2015
DOI: 10.1159/000430253
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β1 Gene Therapy Enhances in Vitro Creation of Tissue-Engineered Cartilage Under Periodic Mechanical Stress

Abstract: Background/Aims: Periodic mechanical stress activates integrin β1-initiated signal pathways to promote chondrocyte proliferation and matrix synthesis. Integrin β1 overexpression has been demonstrated to play important roles in improving the activities and functions of several non-chondrocytic cell types. Therefore, in the current study, we evaluated the effects of integrin β1 up-regulation on periodic mechanical stress-induced chondrocyte proliferation, matrix synthesis and ERK1/2 phosphorylation in chondrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…We previously found that rabbit chondrocytes subjected to stress varying from 0–200 kPa at 0.1 Hz yielded the best quality tissue-engineered cartilage [40]. We accordingly used a pressure range of 0–200 kPa and 0.1 Hz frequency in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that rabbit chondrocytes subjected to stress varying from 0–200 kPa at 0.1 Hz yielded the best quality tissue-engineered cartilage [40]. We accordingly used a pressure range of 0–200 kPa and 0.1 Hz frequency in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…The GAG content of each group was recorded after 6 weeks, as described previously [40]. The samples were rinsed with double-distilled H2O and lyophilized for 12 h, followed by the addition of 1 mL cold H 2 O and incubation at 4°C in a microcentrifuge tube overnight.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this last disadvantage, lentiviruses, belonging to a subclass of retrovirus family derived from the human immunodeficiency virus (HIV), have been proposed because they can transduce in non-dividing cells [76]. Lentivirus were employed for the delivery of sequence that codifies for BMPs [76], zinc-finger protein 145 (ZNF145) [77], IL10 [78] and Integrin-β [79] (Table 1). However, lentiviral vectors, similarly to retroviruses, favour gene integration, which might determine an insertional transformation and, subsequently, tumour formation.…”
Section: Viral Vectormentioning
confidence: 99%
“…Less is known about genes encoding for the cell signalling protein iHH [53,55], for ECM component (COMP) [19] and for integrin β1 [79] (Table 1). COMP is a multidomain homo-pentameric protein, which is an important regulator of collagen fiber assembly, interacting with other matrix proteins and inducing chondrocyte proliferation in vitro.…”
Section: Other Factorsmentioning
confidence: 99%
“…Periodic mechanical stress is advantageous to simulate in vivo physiological conditions for promoting chondrocyte proliferation [1,2]. However, few studies have addressed the mechanisms underlying the translation of such mechanical inputs into biochemical signaling events within the chondrocyte lineage.…”
Section: Introductionmentioning
confidence: 99%